T cells: Bridge-and-channel commute to the white pulp - Sixt, Michael K; Lämmermann, Tim (Immunity)
In contrast to lymph nodes, the lymphoid regions of the spleen—the white pulp—are located deep within the organ, yielding the trafficking paths of T cells in the white pulp largely invisible. In an intravital microscopy tour de force reported in this issue of Immunity, Chauveau et al. show that T cells perform unidirectional, perivascular migration through the enigmatic marginal zone bridging channels.

MAU2 and NIPBL variants impair the heterodimerization of the cohesin loader subunits and cause Cornelia de Lange syndrome - Parenti, Ilaria; Diab, Farah; Gil, Sara Ruiz; Mulugeta, Eskeatnaf; Casa, Valentina; Berutti, Riccardo; Brouwer, Rutger W.W.; Dupé, Valerie; Eckhold, Juliane; Graf, Elisabeth; Puisac, Beatriz; Ramos, Feliciano; et al. (Cell Reports)
The NIPBL/MAU2 heterodimer loads cohesin onto chromatin. Mutations inNIPBLaccount for most cases ofthe rare developmental disorder Cornelia de Lange syndrome (CdLS). Here we report aMAU2 variant causing CdLS, a deletion of seven amino acids that impairs the interaction between MAU2 and the NIPBL N terminus.Investigating this interaction, we discovered that MAU2 and the NIPBL N terminus are largely dispensable fornormal cohesin and NIPBL function in cells with a NIPBL early truncating mutation. Despite a predicted fataloutcome of an out-of-frame single nucleotide duplication inNIPBL, engineered in two different cell lines,alternative translation initiation yields a form of NIPBL missing N-terminal residues. This form cannot interactwith MAU2, but binds DNA and mediates cohesin loading. Altogether, our work reveals that cohesin loading can occur independently of functional NIPBL/MAU2 complexes and highlights a novel mechanism protectiveagainst out-of-frame mutations that is potentially relevant for other genetic conditions.

Synergism of type 1 metabotropic and ionotropic glutamate receptors in cerebellar molecular layer interneurons in vivo - Bao, Jin; Graupner, Michael; Astorga, Guadalupe; Collin, Thibault; Jalil, Abdelali; Indriati, Dwi Wahyu; Bradley, Jonathan; Shigemoto, Ryuichi; Llano, Isabel (eLife)
Type 1 metabotropic glutamate receptors (mGluR1s) are key elements in neuronal signaling. While their function is well documented in slices, requirements for their activation in vivo are poorly understood. We examine this question in adult mice in vivo using 2-photon imaging of cerebellar molecular layer interneurons (MLIs) expressing GCaMP. In anesthetized mice, parallel fiber activation evokes beam-like Cai rises in postsynaptic MLIs which depend on co-activation of mGluR1s and ionotropic glutamate receptors (iGluRs). In awake mice, blocking mGluR1 decreases Cai rises associated with locomotion. In vitro studies and freeze-fracture electron microscopy show that the iGluR-mGluR1 interaction is synergistic and favored by close association of the two classes of receptors. Altogether our results suggest that mGluR1s, acting in synergy with iGluRs, potently contribute to processing cerebellar neuronal signaling under physiological conditions.

Dopamine transporter trafficking and Rit2 GTPase: Mechanism of action and in vivo impact - Fagan, Rita R.; Kearney, Patrick J.; Sweeney, Carolyn G.; Luethi, Dino; Schoot Uiterkamp, Florianne E; Schicker, Klaus; Alejandro, Brian S.; O'Connor, Lauren C.; Sitte, Harald H.; Melikian, Haley E. (Journal of Biological Chemistry)
Following its evoked release, dopamine (DA) signaling is rapidly terminated by presynaptic reuptake, mediated by the cocaine-sensitive DA transporter (DAT). DAT surface availability is dynamically regulated by endocytic trafficking, and direct protein kinase C (PKC) activation acutely diminishes DAT surface expression by accelerating DAT internalization. Previous cell line studies demonstrated that PKC-stimulated DAT endocytosis requires both Ack1 inactivation, which releases a DAT-specific endocytic brake, and the neuronal GTPase, Rit2, which binds DAT. However, it is unknown whether Rit2 is required for PKC-stimulated DAT endocytosis in DAergic terminals or whether there are region- and/or sex-dependent differences in PKC-stimulated DAT trafficking. Moreover, the mechanisms by which Rit2 controls PKC-stimulated DAT endocytosis are unknown. Here, we directly examined these important questions. Ex vivo studies revealed that PKC activation acutely decreased DAT surface expression selectively in ventral, but not dorsal, striatum. AAV-mediated, conditional Rit2 knockdown in DAergic neurons impacted baseline DAT surface:intracellular distribution in DAergic terminals from female ventral, but not dorsal, striatum. Further, Rit2 was required for PKC-stimulated DAT internalization in both male and female ventral striatum. FRET and surface pulldown studies in cell lines revealed that PKC activation drives DAT-Rit2 surface dissociation and that the DAT N terminus is required for both PKC-mediated DAT-Rit2 dissociation and DAT internalization. Finally, we found that Rit2 and Ack1 independently converge on DAT to facilitate PKC-stimulated DAT endocytosis. Together, our data provide greater insight into mechanisms that mediate PKC-regulated DAT internalization and reveal unexpected region-specific differences in PKC-stimulated DAT trafficking in bona fide DAergic terminals.

Clusters in separated tubes of tilted dipoles - Armstrong, Jeremy R.; Jensen, Aksel S.; Volosniev, Artem; Zinner, Nikolaj T. (Mathematics)
A few-body cluster is a building block of a many-body system in a gas phase provided the temperature at most is of the order of the binding energy of this cluster. Here we illustrate this statement by considering a system of tubes filled with dipolar distinguishable particles. We calculate the partition function, which determines the probability to find a few-body cluster at a given temperature. The input for our calculations—the energies of few-body clusters—is estimated using the harmonic approximation. We first describe and demonstrate the validity of our numerical procedure. Then we discuss the results featuring melting of the zero-temperature many-body state into a gas of free particles and few-body clusters. For temperature higher than its binding energy threshold, the dimers overwhelmingly dominate the ensemble, where the remaining probability is in free particles. At very high temperatures free (harmonic oscillator trap-bound) particle dominance is eventually reached. This structure evolution appears both for one and two particles in each layer providing crucial information about the behavior of ultracold dipolar gases. The investigation addresses the transition region between few- and many-body physics as a function of temperature using a system of ten dipoles in five tubes.

On the average-case hardness of total search problems - Kamath Hosdurg, Chethan
A search problem lies in the complexity class FNP if a solution to the given instance of the problem can be verified efficiently. The complexity class TFNP consists of all search problems in FNP that are total in the sense that a solution is guaranteed to exist. TFNP contains a host of interesting problems from fields such as algorithmic game theory, computational topology, number theory and combinatorics. Since TFNP is a semantic class, it is unlikely to have a complete problem. Instead, one studies its syntactic subclasses which are defined based on the combinatorial principle used to argue totality. Of particular interest is the subclass PPAD, which contains important problems like computing Nash equilibrium for bimatrix games and computational counterparts of several fixed-point theorems as complete. In the thesis, we undertake the study of averagecase hardness of TFNP, and in particular its subclass PPAD. Almost nothing was known about average-case hardness of PPAD before a series of recent results showed how to achieve it using a cryptographic primitive called program obfuscation. However, it is currently not known how to construct program obfuscation from standard cryptographic assumptions. Therefore, it is desirable to relax the assumption under which average-case hardness of PPAD can be shown. In the thesis we take a step in this direction. First, we show that assuming the (average-case) hardness of a numbertheoretic problem related to factoring of integers, which we call Iterated-Squaring, PPAD is hard-on-average in the random-oracle model. Then we strengthen this result to show that the average-case hardness of PPAD reduces to the (adaptive) soundness of the Fiat-Shamir Transform, a well-known technique used to compile a public-coin interactive protocol into a non-interactive one. As a corollary, we obtain average-case hardness for PPAD in the random-oracle model assuming the worst-case hardness of #SAT. Moreover, the above results can all be strengthened to obtain average-case hardness for the class CLS ⊆ PPAD. Our main technical contribution is constructing incrementally-verifiable procedures for computing Iterated-Squaring and #SAT. By incrementally-verifiable, we mean that every intermediate state of the computation includes a proof of its correctness, and the proof can be updated and verified in polynomial time. Previous constructions of such procedures relied on strong, non-standard assumptions. Instead, we introduce a technique called recursive proof-merging to obtain the same from weaker assumptions.

Frequency-dependent block of excitatory neurotransmission by isoflurane via dual presynaptic mechanisms - Wang, Han Ying; Eguchi, Kohgaku; Yamashita, Takayuki; Takahashi, Tomoyuki (Journal of Neuroscience)
Volatile anesthetics are widely used for surgery, but neuronal mechanisms of anesthesia remain unidentified. At the calyx of Held in brainstem slices from rats of either sex, isoflurane at clinical doses attenuated EPSCs by decreasing the release probability and the number of readily releasable vesicles. In presynaptic recordings of Ca2+ currents and exocytic capacitance changes, isoflurane attenuated exocytosis by inhibiting Ca2+ currents evoked by a short presynaptic depolarization, whereas it inhibited exocytosis evoked by a prolonged depolarization via directly blocking exocytic machinery downstream of Ca2+ influx. Since the length of presynaptic depolarization can simulate the frequency of synaptic inputs, isoflurane anesthesia is likely mediated by distinct dual mechanisms, depending on input frequencies. In simultaneous presynaptic and postsynaptic action potential recordings, isoflurane impaired the fidelity of repetitive spike transmission, more strongly at higher frequencies. Furthermore, in the cerebrum of adult mice, isoflurane inhibited monosynaptic corticocortical spike transmission, preferentially at a higher frequency. We conclude that dual presynaptic mechanisms operate for the anesthetic action of isoflurane, of which direct inhibition of exocytic machinery plays a low-pass filtering role in spike transmission at central excitatory synapses.

Loss of Ena/VASP interferes with lamellipodium architecture, motility and integrin-dependent adhesion - Damiano-Guercio, Julia; Kurzawa, Laëtitia; Müller, Jan; Dimchev, Georgi A; Schaks, Matthias; Nemethova, Maria; Pokrant, Thomas; Brühmann, Stefan; Linkner, Joern; Blanchoin, Laurent; Sixt, Michael K; Rottner, Klemens; et al. (eLife)
Cell migration entails networks and bundles of actin filaments termed lamellipodia and microspikes or filopodia, respectively, as well as focal adhesions, all of which recruit Ena/VASP family members hitherto thought to antagonize efficient cell motility. However, we find these proteins to act as positive regulators of migration in different murine cell lines. CRISPR/Cas9-mediated loss of Ena/VASP proteins reduced lamellipodial actin assembly and perturbed lamellipodial architecture, as evidenced by changed network geometry as well as reduction of filament length and number that was accompanied by abnormal Arp2/3 complex and heterodimeric capping protein accumulation. Loss of Ena/VASP function also abolished the formation of microspikes normally embedded in lamellipodia, but not of filopodia capable of emanating without lamellipodia. Ena/VASP-deficiency also impaired integrin-mediated adhesion accompanied by reduced traction forces exerted through these structures. Our data thus uncover novel Ena/VASP functions of these actin polymerases that are fully consistent with their promotion of cell migration.

Microwave quantum illumination using a digital receiver - Barzanjeh, Shabir; Pirandola, S.; Vitali, D; Fink, Johannes M (Science Advances)
Quantum illumination uses entangled signal-idler photon pairs to boost the detection efficiency of low-reflectivity objects in environments with bright thermal noise. Its advantage is particularly evident at low signal powers, a promising feature for applications such as noninvasive biomedical scanning or low-power short-range radar. Here, we experimentally investigate the concept of quantum illumination at microwave frequencies. We generate entangled fields to illuminate a room-temperature object at a distance of 1 m in a free-space detection setup. We implement a digital phase-conjugate receiver based on linear quadrature measurements that outperforms a symmetric classical noise radar in the same conditions, despite the entanglement-breaking signal path. Starting from experimental data, we also simulate the case of perfect idler photon number detection, which results in a quantum advantage compared with the relative classical benchmark. Our results highlight the opportunities and challenges in the way toward a first room-temperature application of microwave quantum circuits.

Induced correlations between impurities in a one-dimensional quenched Bose gas - Mistakidis, S. I.; Volosniev, Artem; Schmelcher, P. (Physical Review Research)
We explore the time evolution of two impurities in a trapped one-dimensional Bose gas that follows a change of the boson-impurity interaction. We study the induced impurity-impurity interactions and their effect on the quench dynamics. In particular, we report on the size of the impurity cloud, the impurity-impurity entanglement, and the impurity-impurity correlation function. The presented numerical simulations are based upon the variational multilayer multiconfiguration time-dependent Hartree method for bosons. To analyze and quantify induced impurity-impurity correlations, we employ an effective two-body Hamiltonian with a contact interaction. We show that the effective model consistent with the mean-field attraction of two heavy impurities explains qualitatively our results for weak interactions. Our findings suggest that the quench dynamics in cold-atom systems can be a tool for studying impurity-impurity correlations.

A method for identification of the methylation level of CpG islands from NGS data - Uroshlev, Leonid A.; Abdullaev, Eldar T.; Umarova, Iren R.; Il’Icheva, Irina A.; Panchenko, Larisa A.; Polozov, Robert V.; Kondrashov, Fyodor; Nechipurenko, Yury D.; Grokhovsky, Sergei L. (Scientific Reports)
In the course of sample preparation for Next Generation Sequencing (NGS), DNA is fragmented by various methods. Fragmentation shows a persistent bias with regard to the cleavage rates of various dinucleotides. With the exception of CpG dinucleotides the previously described biases were consistent with results of the DNA cleavage in solution. Here we computed cleavage rates of all dinucleotides including the methylated CpG and unmethylated CpG dinucleotides using data of the Whole Genome Sequencing datasets of the 1000 Genomes project. We found that the cleavage rate of CpG is significantly higher for the methylated CpG dinucleotides. Using this information, we developed a classifier for distinguishing cancer and healthy tissues based on their CpG islands statuses of the fragmentation. A simple Support Vector Machine classifier based on this algorithm shows an accuracy of 84%. The proposed method allows the detection of epigenetic markers purely based on mechanochemical DNA fragmentation, which can be detected by a simple analysis of the NGS sequencing data.

Nonlinear hydrodynamic instability and turbulence in pulsatile flow - Xu, Duo; Varshney, Atul; Ma, Xingyu; Song, Baofang; Riedl, Michael; Avila, Marc; Hof, Björn (Proceedings of the National Academy of Sciences of the United States of America)
Pulsating flows through tubular geometries are laminar provided that velocities are moderate. This in particular is also believed to apply to cardiovascular flows where inertial forces are typically too low to sustain turbulence. On the other hand, flow instabilities and fluctuating shear stresses are held responsible for a variety of cardiovascular diseases. Here we report a nonlinear instability mechanism for pulsating pipe flow that gives rise to bursts of turbulence at low flow rates. Geometrical distortions of small, yet finite, amplitude are found to excite a state consisting of helical vortices during flow deceleration. The resulting flow pattern grows rapidly in magnitude, breaks down into turbulence, and eventually returns to laminar when the flow accelerates. This scenario causes shear stress fluctuations and flow reversal during each pulsation cycle. Such unsteady conditions can adversely affect blood vessels and have been shown to promote inflammation and dysfunction of the shear stress-sensitive endothelial cell layer.

Synthetic spin-orbit coupling mediated by a bosonic environment - Maslov, Mikhail; Lemeshko, Mikhail; Yakaboylu, Enderalp (Physical Review B)
We study a mobile quantum impurity, possessing internal rotational degrees of freedom, confined to a ring in the presence of a many-particle bosonic bath. By considering the recently introduced rotating polaron problem, we define the Hamiltonian and examine the energy spectrum. The weak-coupling regime is studied by means of a variational ansatz in the truncated Fock space. The corresponding spectrum indicates that there emerges a coupling between the internal and orbital angular momenta of the impurity as a consequence of the phonon exchange. We interpret the coupling as a phonon-mediated spin-orbit coupling and quantify it by using a correlation function between the internal and the orbital angular momentum operators. The strong-coupling regime is investigated within the Pekar approach, and it is shown that the correlation function of the ground state shows a kink at a critical coupling, that is explained by a sharp transition from the noninteracting state to the states that exhibit strong interaction with the surroundings. The results might find applications in such fields as spintronics or topological insulators where spin-orbit coupling is of crucial importance.

Localizing grouped instances for efficient detection in low-resource scenarios - Royer, Amélie; Lampert, Christoph (IEEE Winter Conference on Applications of Computer Vision)
State-of-the-art detection systems are generally evaluated on their ability to exhaustively retrieve objects densely distributed in the image, across a wide variety of appearances and semantic categories. Orthogonal to this, many real-life object detection applications, for example in remote sensing, instead require dealing with large images that contain only a few small objects of a single class, scattered heterogeneously across the space. In addition, they are often subject to strict computational constraints, such as limited battery capacity and computing power.To tackle these more practical scenarios, we propose a novel flexible detection scheme that efficiently adapts to variable object sizes and densities: We rely on a sequence of detection stages, each of which has the ability to predict groups of objects as well as individuals. Similar to a detection cascade, this multi-stage architecture spares computational effort by discarding large irrelevant regions of the image early during the detection process. The ability to group objects provides further computational and memory savings, as it allows working with lower image resolutions in early stages, where groups are more easily detected than individuals, as they are more salient. We report experimental results on two aerial image datasets, and show that the proposed method is as accurate yet computationally more efficient than standard single-shot detectors, consistently across three different backbone architectures.

A flexible selection scheme for minimum-effort transfer learning - Royer, Amélie; Lampert, Christoph (2020 IEEE Winter Conference on Applications of Computer Vision)
Fine-tuning is a popular way of exploiting knowledge contained in a pre-trained convolutional network for a new visual recognition task. However, the orthogonal setting of transferring knowledge from a pretrained network to a visually different yet semantically close source is rarely considered: This commonly happens with real-life data, which is not necessarily as clean as the training source (noise, geometric transformations, different modalities, etc.).To tackle such scenarios, we introduce a new, generalized form of fine-tuning, called flex-tuning, in which any individual unit (e.g. layer) of a network can be tuned, and the most promising one is chosen automatically. In order to make the method appealing for practical use, we propose two lightweight and faster selection procedures that prove to be good approximations in practice. We study these selection criteria empirically across a variety of domain shifts and data scarcity scenarios, and show that fine-tuning individual units, despite its simplicity, yields very good results as an adaptation technique. As it turns out, in contrast to common practice, rather than the last fully-connected unit it is best to tune an intermediate or early one in many domain- shift scenarios, which is accurately detected by flex-tuning.

The PBW theorem for affine Yangians - Yang, Yaping; Zhao, Gufang (Transformation Groups)
We prove that the Yangian associated to an untwisted symmetric affine Kac–Moody Lie algebra is isomorphic to the Drinfeld double of a shuffle algebra. The latter is constructed in [YZ14] as an algebraic formalism of cohomological Hall algebras. As a consequence, we obtain the Poincare–Birkhoff–Witt (PBW) theorem for this class of affine Yangians. Another independent proof of the PBW theorem is given recently by Guay, Regelskis, and Wendlandt [GRW18].

Hard antinodal gap revealed by quantum oscillations in the pseudogap regime of underdoped high-Tc superconductors - Hartstein, Máté; Hsu, Yu Te; Modic, Kimberly A; Porras, Juan; Loew, Toshinao; Tacon, Matthieu Le; Zuo, Huakun; Wang, Jinhua; Zhu, Zengwei; Chan, Mun K.; Mcdonald, Ross D.; Lonzarich, Gilbert G.; et al. (Nature Physics)
An understanding of the missing antinodal electronic excitations in the pseudogap state is essential for uncovering the physics of the underdoped cuprate high-temperature superconductors1,2,3,4,5,6. The majority of high-temperature experiments performed thus far, however, have been unable to discern whether the antinodal states are rendered unobservable due to their damping or whether they vanish due to their gapping7,8,9,10,11,12,13,14,15,16,17,18. Here, we distinguish between these two scenarios by using quantum oscillations to examine whether the small Fermi surface pocket, found to occupy only 2% of the Brillouin zone in the underdoped cuprates19,20,21,22,23,24, exists in isolation against a majority of completely gapped density of states spanning the antinodes, or whether it is thermodynamically coupled to a background of ungapped antinodal states. We find that quantum oscillations associated with the small Fermi surface pocket exhibit a signature sawtooth waveform characteristic of an isolated two-dimensional Fermi surface pocket25,26,27,28,29,30,31,32. This finding reveals that the antinodal states are destroyed by a hard gap that extends over the majority of the Brillouin zone, placing strong constraints on a drastic underlying origin of quasiparticle disappearance over almost the entire Brillouin zone in the pseudogap regime7,8,9,10,11,12,13,14,15,16,17,18.

Reconfiguration problems - Masárová, Zuzana
This thesis considers two examples of reconfiguration problems: flipping edges in edge-labelled triangulations of planar point sets and swapping labelled tokens placed on vertices of a graph. In both cases the studied structures – all the triangulations of a given point set or all token placements on a given graph – can be thought of as vertices of the so-called reconfiguration graph, in which two vertices are adjacent if the corresponding structures differ by a single elementary operation – by a flip of a diagonal in a triangulation or by a swap of tokens on adjacent vertices, respectively. We study the reconfiguration of one instance of a structure into another via (shortest) paths in the reconfiguration graph. For triangulations of point sets in which each edge has a unique label and a flip transfers the label from the removed edge to the new edge, we prove a polynomial-time testable condition, called the Orbit Theorem, that characterizes when two triangulations of the same point set lie in the same connected component of the reconfiguration graph. The condition was first conjectured by Bose, Lubiw, Pathak and Verdonschot. We additionally provide a polynomial time algorithm that computes a reconfiguring flip sequence, if it exists. Our proof of the Orbit Theorem uses topological properties of a certain high-dimensional cell complex that has the usual reconfiguration graph as its 1-skeleton. In the context of token swapping on a tree graph, we make partial progress on the problem of finding shortest reconfiguration sequences. We disprove the so-called Happy Leaf Conjecture and demonstrate the importance of swapping tokens that are already placed at the correct vertices. We also prove that a generalization of the problem to weighted coloured token swapping is NP-hard on trees but solvable in polynomial time on paths and stars.
Keywords: reconfiguration; reconfiguration graph; triangulations; flip; constrained triangulations; shellability; piecewise-linear balls; token swapping; trees; coloured weighted token swapping

The Arabidopsis NRT1.1 transceptor coordinately controls auxin biosynthesis and transport to regulate root branching in response to nitrate - Maghiaoui, A; Bouguyon, E; Cuesta, Candela; Perrine-Walker, F; Alcon, C; Krouk, G; Benková, Eva; Nacry, P; Gojon, A; Bach, L (Journal of Experimental Botany)
In agricultural systems, nitrate is the main source of nitrogen available for plants. Besides its role as a nutrient, nitrate has been shown to act as a signal molecule for plant growth, development and stress responses. In Arabidopsis, the NRT1.1 nitrate transceptor represses lateral root (LR) development at low nitrate availability by promoting auxin basipetal transport out of the LR primordia (LRPs). In addition, our present study shows that NRT1.1 acts as a negative regulator of the TAR2 auxin biosynthetic gene expression in the root stele. This is expected to repress local auxin biosynthesis and thus to reduce acropetal auxin supply to the LRPs. Moreover, NRT1.1 also negatively affects expression of the LAX3 auxin influx carrier, thus preventing cell wall remodeling required for overlying tissues separation during LRP emergence. Both NRT1.1-mediated repression of TAR2 and LAX3 are suppressed at high nitrate availability, resulting in the nitrate induction of TAR2 and LAX3 expression that is required for optimal stimulation of LR development by nitrate. Altogether, our results indicate that the NRT1.1 transceptor coordinately controls several crucial auxin-associated processes required for LRP development, and as a consequence that NRT1.1 plays a much more integrated role than previously anticipated in regulating the nitrate response of root system architecture.

The CEP5 peptide promotes abiotic stress tolerance, as revealed by quantitative proteomics, and attenuates the AUX/IAA equilibrium in Arabidopsis - Smith, S; Zhu, S; Joos, L; Roberts, I; Nikonorova, N; Vu, LD; Stes, E; Cho, H; Larrieu, A; Xuan, W; Goodall, B; van de Cotte, B; et al. (Molecular & Cellular Proteomics)
Peptides derived from non-functional precursors play important roles in various developmental processes, but also in (a)biotic stress signaling. Our (phospho)proteome-wide analyses of C-terminally encoded peptide 5 (CEP5)-mediated changes revealed an impact on abiotic stress-related processes. Drought has a dramatic impact on plant growth, development and reproduction, and the plant hormone auxin plays a role in drought responses. Our genetic, physiological, biochemical and pharmacological results demonstrated that CEP5-mediated signaling is relevant for osmotic and drought stress tolerance in Arabidopsis, and that CEP5 specifically counteracts auxin effects. Specifically, we found that CEP5 signaling stabilizes AUX/IAA transcriptional repressors, suggesting the existence of a novel peptide-dependent control mechanism that tunes auxin signaling. These observations align with the recently described role of AUX/IAAs in stress tolerance and provide a novel role for CEP5 in osmotic and drought stress tolerance.